2021
DOI: 10.1111/bjd.20653
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra for palmoplantar pustulosis: results from a randomized, double‐blind, multicentre, two‐staged, adaptive placebo‐controlled trial (APRICOT)*

Abstract: Background Palmoplantar pustulosis (PPP) is a rare, debilitating, chronic inflammatory skin disease that affects the hands and feet. Clinical, immunological and genetic findings suggest a pathogenic role for interleukin (IL)-1. Objectives To determine whether anakinra (an IL-1 receptor antagonist) delivers therapeutic benefit in PPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Table 3 contains information about the main recent clinical trials regarding treatment of PP [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 ]. Ongoing clinical trials and other completed studies not included in Table 3 are reported in Table 4 .…”
Section: Treatmentmentioning
confidence: 99%
“…Table 3 contains information about the main recent clinical trials regarding treatment of PP [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 ]. Ongoing clinical trials and other completed studies not included in Table 3 are reported in Table 4 .…”
Section: Treatmentmentioning
confidence: 99%
“…Regarding the evaluation of NPV, we suggest the authors employ ICD codes for all dermatology (ICD-10 L20-L30) 3 and the symptom of rash (e.g. ICD-10 T80Á6) to identify cases, and then review the record and evaluate the NPV.…”
Section: Response To 'mentioning
confidence: 99%
“…Completed trials are summarized in Table 3. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The first UK DCTN trial was on antibiotics to prevent cellulitis recurrences, and exemplifies the aims of the network. The idea came from a busy district hospital dermatologist (the late Dr Neil Cox 31 ) and evaluated a low-cost intervention (generic penicillin V) that is of little interest to industry, assessing it for a serious disease that did not seem to belong to any specialism.…”
Section: Where Do Patients Come Into It All?mentioning
confidence: 99%